Answer:
f(g(x))=6x-8
Explanation:
To keep it simple lets say if , for example
![f(x)=2x-4](https://img.qammunity.org/2021/formulas/mathematics/high-school/60vqzrs0dc2pu87y3oqfl7qhljc8bv4o7h.png)
then f(2) would be what?
![f(2)=2(2)-4\\f(2)=0](https://img.qammunity.org/2021/formulas/mathematics/college/sb32b83hxjqmlv9cdw93ph4xu868tn1pi4.png)
which means we plugged in x=2 in our f(x) this goes for same as the composite function
where we plug in g(x) in f(x) and replace x with g(x). I'll show you
![f(x)=2x-4\\g(x)=-3x+2\\](https://img.qammunity.org/2021/formulas/mathematics/college/rjj6ppdldzz87lf8hg8q3ia15fg4rh6tm7.png)
now we insert g(x) in f(x) cause we need f(g(x)) which means we replace x with the function g(x).
![f(g(x))=-2(-3x+2)-4](https://img.qammunity.org/2021/formulas/mathematics/college/a52qwoexa6hiced05i1jqw2t05am5gyg0x.png)
![f(g(x))=6x-4-4\\f(g(x))=6x-8](https://img.qammunity.org/2021/formulas/mathematics/college/ck2huiktdkyiiiwp9o6qo680ds7b7p0fmp.png)
so that is our final answer.
Hope i helped